2019
DOI: 10.1021/acs.orglett.9b00378
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Constrained Tetracyclic Peptides by Consecutive CEPS, CLIPS, and Oxime Ligation

Abstract: In Nature, multicyclic peptides constitute a versatile molecule class with various biological functions. For their pharmaceutical exploitation, chemical methodologies that enable selective consecutive macrocyclizations are required. We disclose a combination of enzymatic macrocyclization, CLIPS alkylation, and oxime ligation to prepare tetracyclic peptides. Five new small molecular scaffolds and differently sized model peptides featuring noncanonical amino acids were synthesized. Enzymatic macrocyclization, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 37 publications
(61 reference statements)
0
21
0
Order By: Relevance
“…291 Showcasing the versatility of having a set of chemoselective reactions, several efforts have successfully obtained multicyclic peptides by combining different cyclisation strategies, such as CuAAC, enzymatically-mediated lactamization, oxime ligations, or thioether formation on scaffolds, yielding structurally unique moieties. [305][306][307] 10.2 1,5-Disubstituted 1,2,3-triazole formation: rutheniumcatalyzed azide-alkyne cycloaddition A 1,5-disubstiuted 1,2,3-triazole is similar to an E-amide bond in terms of H-bond acceptor and donor positions and can function as a bioisostere for it. Additionally, as the C α -C α distance in a 1,5-substituted triazole formed between β-azidohomoalanine and propargyl glycine is similar to the C α -C α distance in a cysteine disulfide (4.1-4.2 Å versus 3.9-4.0 Å), it has also attracted substantial interest as a disulfide mimetic (Scheme 35, right).…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
“…291 Showcasing the versatility of having a set of chemoselective reactions, several efforts have successfully obtained multicyclic peptides by combining different cyclisation strategies, such as CuAAC, enzymatically-mediated lactamization, oxime ligations, or thioether formation on scaffolds, yielding structurally unique moieties. [305][306][307] 10.2 1,5-Disubstituted 1,2,3-triazole formation: rutheniumcatalyzed azide-alkyne cycloaddition A 1,5-disubstiuted 1,2,3-triazole is similar to an E-amide bond in terms of H-bond acceptor and donor positions and can function as a bioisostere for it. Additionally, as the C α -C α distance in a 1,5-substituted triazole formed between β-azidohomoalanine and propargyl glycine is similar to the C α -C α distance in a cysteine disulfide (4.1-4.2 Å versus 3.9-4.0 Å), it has also attracted substantial interest as a disulfide mimetic (Scheme 35, right).…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
“…In the first, they accomplished a one-pot cyclization and oxidative folding of various cysteine-rich miniproteins (cyclotides and defensins) at a multi-gram scale [ 57 ]. In the second, regioselective synthesis of constrained tetracyclic peptides was achieved by taking advantage of orthogonal succeeding CEPS, CLIPS, and oxime ligations [ 58 ]. For oxime ligation (the condensation reaction between an aminooxy group and a carbonyl electrophile), the aminooxy group was introduced in the peptide itself using an artificial amino acid aminooxy-homoserine, while the protected carbonyl groups were instilled via tetradentate bromide CLIPS crosslinkers.…”
Section: Constrainment Strategies and Chemistriesmentioning
confidence: 99%
“…Such binding sites are deemed undruggable with conventional small molecular weight com-Figure 7. Three-stage macrocyclization of unprotected peptides, combining chemo-enzymatic peptide synthesis using omniligase-1 (CEPS), chemical ligation of peptides onto scaffolds (CLIPS), and oxime ligation (adapted from [58]). Two distinct strategies are depicted, differing in CLIPS crosslinkers and cognate residues harboring orthogonally reactive functional groups.…”
Section: Peptide Staplingmentioning
confidence: 99%
“…It was shown that due to the broad substrate scope and traceless ligation, different sites could be used to synthesize the cyclic peptides. Most recently, the cyclization technology was combined with small organic scaffolds and other ligation technologies such as oxime ligation and click chemistry (Richelle et al, 2018; Streefkerk et al, 2019). Combining enzymatic and chemical ligation technologies, tetracyclic peptides could be synthesized in a one pot fashion that poses two distinct biological activities.…”
Section: Subtilisin-derived Variantsmentioning
confidence: 99%